Impact of Earthquakes on Women's Daily Life in Kathmandu - Pokharel, Saroj (Journal of Janta Multiple Campus, 2025)
The natural phenomena of 2015 earthquake particularly affect in women daily routine and provide threat. As women were given responsibility of caretaker they face tremendous challenge in their living, protection, physical and mental health. Among various research approach descriptive method was used to take qualitative data from the women who had first experience of earthquake. Moreover, checklists were used in stability of data taken from ethnographic observation and interviews. During the earthquake of 2015 it causes destruction of homes forcing women in movement from one place to another with most of the time spending in temporary shelters. Women are main caregiver for family members, so they are facing depreciation of food and emotional stress. For responding such stressful situations different types of therapy, meditation and social mobilization in community play tremendous role. Although women have such type of difficulty during earthquake they were highly engaged in reformation of their home and society by taking strong decisions. During earthquake particularly the life of all inhabitants were affected but it turned women into their roles and responsibility. However, the problems such as absence of resources, physical and mental health problem and weak economy remain as it is. The wants of women must be taken as priority which not only handle the present scenario but also helps in future activities, making them more enthusiastic in their work and help in taking strong decision process for long term achievement.